PENGARUH HAFALAN AL-QUR’AN TERHADAP KECERDASAN INTELEKTUAL PESERTA DIDIK KELAS VIII DI MADRASAH TSANAWIYAH SEPATAN KECAMATAN SEPATAN KABUPATEN TANGERANG - Sudrajat, Sanin (Jurnal Ilmiah Pendidikan dan Keislaman, 2023)
This research discusses the influence of memorizing the Al-Qur'an which is variable the reason the researcher chose this title was because in implementing the Al-Qur'an memorization program at MTs Sepatan, class VIII students were different in mastering Al-Qur'an memorization. There were those who achieved the specified target, there were also those who did not reach the specified target, namely from Surah Al-Qari'ah to Surah Al-Balad. In this case, it also shows that the intelligence and memorization abilities of students also vary. Intelligent students will easily and quickly memorize the Al-Qur'an, while students with average intelligence will experience difficulty in memorizing the Al-Qur'an and will need a long time to complete the memorization. So, according to the author, research needs to be conducted to prove whether memorizing the Al-Qur'an can influence intellectual intelligence or not. The method used in this research is descriptive analytical with a quantitative approach and using the product moment correlation formula to obtain or collect data, facts and information related to the variables being discussed in the research (X and Y). The population in the research was 53 class VIII students at Madrasah Tsanawiyah Sepatan, with data obtained based on observation, distribution of questionnaires, and literature study. The results of the one-party test or t count > t table are 2.85 > 1.671 with an error rate of 5% (0.05) which means Ho is rejected and Ha is accepted. And with a level of influence of 14% = 0.14 and the remaining 86% = 0.86 influenced by other factors not studied. Therefore, the research results show that there is a positive influence between memorizing the Koran on the intellectual intelligence of class VIII students at the Sepatan Tsanawiyah Madrasah, Sepatan District, Tangerang Regency, although it is still relatively low because it is located in the correlation interval between 0.20 - 0.399.